2016
DOI: 10.1093/ajcp/aqw034
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Tumor Microenvironment in Diffuse Large B-Cell Lymphoma Uniformly Treated With R-CHOP Chemotherapy

Abstract: The concomitant evaluation of cell of origin along with tumor microenvironment components identifies patients with DLBCL treated with R-CHOP chemotherapy portraying a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…The mean MVD in the RCHOP group with events was 154.7/mm 2 and that in the CHOP group was 349.2/mm. 2 Median of CD34 was 37 in a study by Ruan et al 11 Our findings correlate with the study by Perry et al, who attempted to simulate the stromal-2 signature by measuring MVD in DLBCL and found high MVD to be an unfavorable prognostic factor. 14 The stromal-2 signature is expressed by genes regulating endothelial proliferation through vascular endothelial growth factor (VEGF) receptor, TEK (tyrosine kinase, endothelial), and ERG V-ets (erythroblastosis virus E26 oncogene homolog gene).…”
Section: Fig 1 Immunohistochemistry For Cd34 Highlighting Microvessesupporting
confidence: 87%
See 2 more Smart Citations
“…The mean MVD in the RCHOP group with events was 154.7/mm 2 and that in the CHOP group was 349.2/mm. 2 Median of CD34 was 37 in a study by Ruan et al 11 Our findings correlate with the study by Perry et al, who attempted to simulate the stromal-2 signature by measuring MVD in DLBCL and found high MVD to be an unfavorable prognostic factor. 14 The stromal-2 signature is expressed by genes regulating endothelial proliferation through vascular endothelial growth factor (VEGF) receptor, TEK (tyrosine kinase, endothelial), and ERG V-ets (erythroblastosis virus E26 oncogene homolog gene).…”
Section: Fig 1 Immunohistochemistry For Cd34 Highlighting Microvessesupporting
confidence: 87%
“…The study by Gomez-Gelvez et al showed that CD34 is the best stain owing to its clean background, and positive staining cells/cell groups with or without lumen formation represent microvessels. 2 Therefore, we too did CD34 staining and counting using image analysis. MVD is the measure used to assess the angiogenesis in tumors including lymphomas.…”
Section: Fig 1 Immunohistochemistry For Cd34 Highlighting Microvessementioning
confidence: 99%
See 1 more Smart Citation
“…One of the main functions of Tregs is the regulation of antitumor immune responses by inhibiting the cytokine production and suppressing the proliferation of CD8 + T cells, which may lead to an ineffective antitumor response and to the proliferation of cancer cells [37][38][39]. In DLBCL, the prognostic influence of FOXP3 + Treg is controversial, reported as being associated with a good prognosis in some studies or with an adverse outcome [40][41][42] or a trend toward a worse prognosis in other studies [43].…”
Section: Immune Evasionmentioning
confidence: 99%
“…The mechanisms by which mast cells reduce the efficacy of antibody-based therapies in FL remain to be determined and might include the negative regulation of macrophage activity and antibody-dependent cellular cytotoxicity through the expression of Fc receptors which can engage rituximab [62]. Tissue microarray immunohistochemistry with automated scoring of FoxP3, CD68 and microvessel (CD34) density (MVD) has been shown to stratify patients with DLBCL into risk groups and to predict prognosis [66]. Patients in the high-risk group had significantly worse EFS and PFS, suggesting that TME components should be considered as an important tool to predict patient survival.…”
Section: Chronic Myeloid Leukaemia Targeted Treatment With Tyrosine mentioning
confidence: 99%